2010
DOI: 10.1111/j.1442-2042.2010.02613.x
|View full text |Cite
|
Sign up to set email alerts
|

Updated Japanese Urological Association Guidelines on prostate‐specific antigen‐based screening for prostate cancer in 2010

Abstract: Abstract:The exposure rate of screening for prostate cancer using prostate-specific antigen (PSA) in Japan is still very low compared with that in the USA or western Europe. The mortality rate of prostate cancer will increase in the future and in 2020 it will be 2.8-fold higher than in 2000. Therefore, there is an urgent need to determine the best available countermeasures to decrease the rate of prostate cancer death. PSA screening, which can reduce the risk of death as a result of prostate cancer, should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…In other words, PSA was added to hematological parameters, and screening was continued. As the screening item is noninvasive in comparison with other cancer screenings, the number of self-governing bodies in which PSA screening was introduced increased 5-fold (71.2% of the cities/towns/villages of Japan according to a survey in 2006) during a 6-year period in Japan [4]. With the increase of PSA screening programs in our country, the propaganda ‘Early detection is the only way to save life' has been spread accordingly without the information of informed decision making.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, PSA was added to hematological parameters, and screening was continued. As the screening item is noninvasive in comparison with other cancer screenings, the number of self-governing bodies in which PSA screening was introduced increased 5-fold (71.2% of the cities/towns/villages of Japan according to a survey in 2006) during a 6-year period in Japan [4]. With the increase of PSA screening programs in our country, the propaganda ‘Early detection is the only way to save life' has been spread accordingly without the information of informed decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Between 1995 and 2010, a total of 65,513 men (including repeated screenees) participated in this program, and prostate cancer was diagnosed in 520 men (0.8%). Between 2009 and 2010, we conducted the survey using Fact Sheet (table 1) after the primary screening [4] published by the Japanese Urological Association.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSA-based screening systems for PCA have not been established by the Japanese government, but mostly administered by municipal governments since the 1990s. The Japanese Urological Association (JUA) recommends PSA-based screening for men over 50 years old, and also further examinations for patients with more than 4 ng/mL or age-adjusted cut off levels of PSA to assess the presence of PCAs [2]. Further examinations including digital rectal examinations, transrectal ultrasonography, blood examinations, magnetic resonance imaging, and/or prostate biopsy are performed as secondary screening.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, PC will be the leading cause of cancer morbidity in the near future and the mortality rate of PC in 2020 is anticipated to be 2.8-fold higher than it was in 200012. Since Huggins and Hodges showed that surgical castration suppresses PC progression, it has been clear that androgen biosynthesis is important to the growth and survival of PC cells3.…”
mentioning
confidence: 99%